분화된 C2C12 근관에서 HDAC 조절을 통한 근감소증 개선 물질 도출 - 김유진 (The Graduate School, Ajou University, 2024)
근감소증(Muscle Atrophy)은 근조직 외부 및 내부의 환경 변화로 인해 근육 량과 근조직의 크기가 감소된 것을 의미한다. 최신 연구에서 histone deacetylase (HDAC)의 발현 및 활성 변화가 근감소증과 연관되어 있다는 내 용이 연달아 발표된 바 있다. HDAC는 세포 내에서 히스톤 단백질에 결합하고 표적 단백질의 acetylation을 제거하여 후성적으로 유전자 발현을 조절하는 단 백질로, 탈신경화 된 골격근에서 HDAC의 클래스 중 HDAC4와 5의 발현이 증 가되는데 HDAC4와 5의 발현이 감소하였을 때 근감소증이 개선된다고 보고된 것이다. 본 연구자는 근감소증이 유발된 모델들(제2형 당뇨병 환자, DEX 처치 한 마우스)에서 HDAC4와 5가 증가되어 있음을 확인하고, HDAC4 억제를 통 한 근감소증 억제 약물을 도출하고자 다음과 같이 실험을 진행하였다. 첫째, 4,480종의 약물들에 대해 HDAC4 assay (in vitro)를 진행하였고, 그 결과 유 의적으로 HDAC4 억제 효과가 있는 7종의 약물(7-aminocarboxycoumarin 2, silver sulfadiazine, voxtalisib, cyclizine 2HCl, benurestat, 1,4- Naphthoquinone, LMK-235)을 선별하였다. 둘째, 분화된 C2C12 myotubes 에 dexamethasone(DEX) 처치하여 MuRF1, atrogin-1, myostatin 증가, IGF-1을 감소시키는 in cell 근감소증 모델을 구축하였다. 셋째, HDAC4 억제 효과가 있는 약물들의 근감소증 억제 유효성 검사를 진행하였다. 그 결과, 선별 된 7종 약물들은 DEX로 인해 증가한 myostatin의 발현을 감소시켰다. 흥미롭 게도 LMK-235는 MuRF1의 발현을 감소시켰을 뿐 아니라, 억제된 IGF-1의 발현을 회복시켰다. 또한 LMK-235 단독으로 처치한 경우 근분화를 촉진시키 는 미토콘드리아 생합성 관련 유전자(PGC-1a, TFAM, NRF2, SOD2)와 미토 콘드리아 복합체 구성 요소 유전자(ATP5a1, SDHB, COX2)의 발현을 증가시 켰다. 그리고 근 생성 관련 유전자인 MEF2C와 MYH2의 발현 역시 증가시킨 것 을 확인하였다. 따라서 본 연구를 통해 새로운 HDAC4 억제제를 발견하였고 이러한 억제제가 근감소증 모델에서 근감소증 유발 유전자 발현을 억제하는 것을 확인하였다. 즉 HDAC4는 근감소증 치료제의 타깃이 될 수 있으며 HDAC4의 억제는 근감소증 을 개선할 수 있을 것으로 추정된다. 핵심 단어: 근감소증, HDAC, HDAC Inhibitor|Muscle atrophy refers to the reduction in muscle mass and size due to changes in the external and internal environment of muscle tissue. Recent studies have continuously reported that changes in the expression and activity of histone deacetylase (HDAC) are associated with muscle atrophy. HDAC is a protein that binds to histone proteins within cells and epigenetically regulates gene expression by removing acetylation from target proteins. It has been observed that in denervated skeletal muscles, the expression of HDAC4 and HDAC5, among the HDAC classes, is increased. When the expression of HDAC4 and HDAC5 is reduced, muscle atrophy is reportedly improved. In this study, the researcher confirmed that HDAC4 and HDAC5 are increased in models induced with muscle atrophy (type 2 diabetes patients, DEX-treated mice). To identify HDAC4 inhibitors as potential therapeutic agents for muscle atrophy, the following experiments were conducted: First, an HDAC4 assay (in vitro) was performed on 4,480 drugs, resulting in the selection of seven drugs (7-aminocarboxycoumarin 2, silver sulfadiazine, voxtalisib, cyclizine 2HCl, benurestat, 1,4-Naphthoquinone, LMK-235) that significantly inhibited HDAC4. Second, a cell-based muscle atrophy model was established by treating differentiated C2C12 myotubes with dexamethasone (DEX), which increased the expression of MuRF1, atrogin-1, and myostatin while decreasing IGF-1. Third, the efficacy of the selected HDAC4 inhibitors in inhibiting muscle atrophy was tested. As a result, the seven selected drugs reduced the expression of myostatin increased by DEX. Interestingly, LMK-235 not only decreased the expression of MuRF1 but also restored the expression of suppressed IGF-1. Additionally, when treated with LMK-235 alone, it promoted muscle differentiation by increasing the expression of mitochondrial biogenesis-related genes (PGC-1a, TFAM, NRF2, SOD2) and mitochondrial complex component genes (ATP5a1, SDHB, COX2). The expression of muscle generation-related genes, MEF2C and MYH2, was also increased. Therefore, this study discovered new HDAC4 inhibitors and confirmed that these inhibitors suppressed the expression of genes that induce muscle atrophy in muscle atrophy models. In other words, HDAC4 could be a target for muscle atrophy treatment, and the inhibition of HDAC4 is expected to improve muscle atrophy. Keyword: Muscle Atrophy, HDAC, HDAC Inhibitor
학위논문(석사)--의생명과학과,2024. 8
Keywords: HDAC; HDAC inhibitor; 근감소증